Prevalence of Depression Symptoms and its Effective Factors in Pregnant Women - Ali Gholami; Sadaf Ahmadpoor; Behnam Baghban; Sajjad Kheirtalab; Zohreh Foroozanfar (Guilan University of Medical Sciences, 2016)
Abstract Introduction: Living with schizophrenic patients is stressful. Caregivers without sufficient knowledge cannot perform their responsibilities very well. This situation leads to relapse and re-hospitalization. Families experience a lot of stress facing such difficult situations which results in discomfort, tensions or despair in family members. High tensions impair family function unless the family adapt to the new situation. Objective: This study aimed to determine effectiveness of stress coping skills training with psycho-educational approach among caregivers` of schizophrenic patients on family function and psychological well-being. Methods: This is an experimental study with pretest-post test design and a control group comprising of main following variables; coping skills training with a psycho-educational approach(the independent variable) and family function and psychological well-being (two dependent variables). The study population included 220 caregivers of patients with schizophrenia who had referred to psychiatric clinic and had a history of hospitalization. Since the number of members in a psychotherapy group should be very limited, the sample size was considered 30. Sampling was performed with convenience method. Data collection tools included Ryff Psychological Well-Being and Family Assessment Device questionnaires. The psychometrics of both questionnaires had been confirmed in Iran. Ryff assesses six main components of psychological well-being. Therefore, it has 6 subscales (each subscale contains 14 items) and 84 items. The subjects specified their level of agreement, "agree "to" disagree", in a 6-point Likert scale. To obtain a score for each subscale, the score of each item on the related subscale should be summed. The total score of all 84 items equals the total psychological well-being. The subscales include self-acceptance, positive relations with others, autonomy, environmental mastery, purposeful life and personal growth. Family Assessment Device is a questionnaire with 60 items in domains of problem-solving, relationships, roles, effective response, effective involvement, behavior control, and general functioning. They were answered in a 4-Likert scale. In order to obtain the score of each subscale, all subscale scores have to be added then divided by number of items of each subscale. Higher scores show poor functioning. In this study, the mean score was used to compare the groups. The researcher referred to the psychiatry clinic and specified the records of patients diagnosed with schizophrenia and had the inclusion criteria; being main caregiver, educated and living in Rasht. The families were then contacted.30 patients were randomly selected whose psychological well-being and family function score had one SD below the mean of questionnaires scores. They were placed in two experimental and control groups (15 per group). During the intervention, six subjects (3 per group) withdrew due to family problems and the disease recurrence. Again in the last session, the questionnaires were completed by the subjects. The interventions were performed twice a week for 90 minutes in twelve consecutive sessions. Homogeneity of the two groups in terms of evaluated variables was approved using ANOVA. Then, the variance-covariance analysis was used to determine the effectiveness of stress coping skill straining with psyche-educational approach on variables of family function and psychological well-being. Results: Most of the subjects (58.3%) were women with mean age of 53.9±5.87. Majority of them (79.2%) had secondary education. Analysis of data showed that the mean score of family function in the experimental group in pretest was 183.42± 13.96 and 177.08±8.23 in the control group. The mean score of the psychological well-being was 224.58±27.03 in the experimental and 228.33± 12.01in the control group. In the posttest, the mean score of family function equaled121.83±15.59 and the control group 172.58±4.25. Moreover, in the post test the mean of psychological well-being of the experimental group and the control group were 373.33±23.96 and 242.67±7.27, respectively. Analysis of variance test with Wilks' lambda to determine the effectiveness of stress coping skills training on family function and psychological well-being in combination, indicated the significant impact of education (p<0.0001). Using ANOVA confirmed the significant effect of these training on family function (p<0.0001) and psychological well-being (p<0.0001) as well. Stress coping skills training with the psycho-educational approach is effective on family function and psycho-educational well-being in caregivers of schizophrenic patients.